Implementation of Reward and Punishment in Enhancing Motivation for Learning Indonesian Language at MIS Ulumul Qur’an Medan (Literasi Nusantara, 2023)
This research aims to explore various aspects of Indonesian language learning at MIS Ulumul Qur'an Medan. The objectives include investigating the application of rewards and punishment, understanding their impact on student motivation, and evaluating how these strategies contribute to increased motivation in learning Indonesian. Conducted at MIS Ulumul Qur'an Medan, the research adopts a qualitative approach with a descriptive method, utilizing observation, interviews, and documentation for data collection. The analysis involves data reduction, presentation, and drawing conclusions. The findings reveal that rewards, such as praise, stationery, and food, are applied by teachers when students demonstrate positive actions, answer quizzes, or complete assigned notes. Conversely, punishments, including warnings, standing, or singing in front of the class, are employed when students violate established rules. Moreover, the research emphasizes the crucial role of reward- and punishment-based learning motivation in influencing student behavior. Students tend to emulate observed actions, making these approaches valuable tools for shaping positive learning attitudes. Ultimately, the application of rewards and punishment significantly contributes to heightened student motivation. Students exhibit increased enthusiasm for learning, a positive attitude toward attending school, a liking for the subject, and improved participation in answering questions posed by the teacher. These outcomes underscore the effectiveness of utilizing rewards and punishment as motivational tools in Indonesian language learning at MIS Ulumul Qur'an Medan.
Keywords: Reward; Punishment; Motivation